Cost-Effectiveness and Budget Impact of Emerging Minimally Invasive Surgical Treatments for Benign Prostatic Hyperplasia - Bilal Chughtai; Sirikan Rojanasarot; Kurt Neeser; Dmitry Gultyaev; Stacey L. Amorosi; Neal D. Shore (Journal of Health Economics and Outcomes Research)
**Background:** Benign prostatic hyperplasia (BPH) is one of the most prevalent and costly chronic conditions among middle-aged and elderly men. Prostatic urethral lift (PUL) and convective water vapor thermal therapy (WVTT) are emerging minimally invasive surgical treatments as an alternative to traditional treatment options for men with moderate-to-severe BPH. This study evaluated the cost-effectiveness and budget impact of PUL and WVTT for men with BPH using long-term clinical outcomes.